Safety of pyrroloquinoline quinone disodium salt as a novel food pursuant to Regulation (EC) No 258/97. (20th November 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on pyrroloquinoline quinone disodium salt (PQQ), trade name BioPQQ™, as a novel food pursuant to Regulation (EC) No 258/97. PQQ is produced by fermentation using Hyphomicrobium denitrificans CK‐275 and purification process. PQQ has a minimum purity of 99.0%. The information provided on the composition, specifications, batch‐to‐batch variability, stability and production process of PQQ is sufficient and does not raise safety concerns. The applicant intends to market PQQ for use in food supplements for healthy adults, except pregnant and lactating women, at a maximum proposed level of consumption of 20 mg/day (corresponding to 0.29 mg/kg bw per day for a 70‐kg person). The proposed level of consumption is at least 250 times higher than the estimated background intake of PQQ occurring naturally in foods. Information on the absorption, distribution, metabolism and excretion of PQQ in animals and humans is limited. Considering the no‐observed‐adverse‐effect‐level (NOAEL) of 100 mg/kg bw per day from a 90‐day repeated dose oral toxicity study with BioPQQ™, and the maximum proposed level of consumption, the Panel concludes that the margin of exposure (of 344) is sufficient. The Panel concludes that the novel food, pyrroloquinoline quinone disodium salt (BioPQQ™), is safe under the intended conditions of use as specified by the applicant.